E-merit - the development of responsive web-based merit point system for Delima Residential College UiTM Shah Alam - Roslan, Muhammad Rabbani (2019)
The project is about the development of a responsive web-based merit point system for residents Delima college UiTM Shah Alam. There are some problems that lead to this project which are the current point system working for Delima college is available in offline and can be access by administration only while the cost of maintaining the system is also quite expensive where the college management has to buy a few barcode readers to ensure a current system can run smoothly and work efficiently. The objectives of this project are to identify the requirement, to design and to develop the development of Responsive Web-Based Merit Point System for Residents Delima College UiTM Shah Alam. The scope for this project is a system divided into two types of access, which are user and administrator. This project is to develop a webbased application for tracking accumulative merit points of college activities obtained by the residents using the technology of QR code where generated within administrator functions.